The factors that impact the total productivity in Malaysia / Maziah Busrah - Busrah, Maziah (2014)
This study attempts to determine the factors that impact the Total Factor Productivity (TFP) in Malaysia during 1970 until 2011. The growth of Total Factor Productivity (TFP) can give society opportunity to raise the welfare of the people. Thus, many researchers argue on determinants of the Total Factor Productivity whether the input driven, technology-driven or productivity-driven. The problem of this study is which the factor that give more impacts to the Total Factor Productivity. The data will be regress by Transformation data into Logarithm (LOG), Ordinary Least Square (OLS) Test, Augmented Dickey-Fuller (ADF) Unit Root Test, Autocorrelation Test and Granger Causality Cause Test. Based on the result by regress all the data on Eviews6, independent variables and dependent variable has a significant relationship and Trade Openness give more impact to the Total Factor Productivity (TFP). The recommendation for this paper is Malaysia is more focus on technology-driven and productivity-driven in order to increase economic growth in long term.